Specific Gene Expression and Epigenetics 2014
DOI: 10.1201/b16680-4
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 Gene Expression in Colon Cancer Tissue Related to Regulating Factors and Promoter Methylation Status

Abstract: Background: Increased cyclooxygenase activity promotes progression of colorectal cancer, but the mechanisms behind COX-2 induction remain elusive. This study was therefore aimed to define external cell signaling and transcription factors relating to high COX-2 expression in colon cancer tissue.Method: Tumor and normal colon tissue were collected at primary curative operation in 48 unselected patients. COX-2 expression in tumor and normal colon tissue was quantified including microarray analyses on tumor mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…Asting et al focused on defining external cell signaling and transcription factors relating to high COX-2 expression in colon cancer cells. High COX-2 expression has been connected with large differences in gene expression compared with normal colon mucosa and low COX-2 expression cells [32]. This observation indicates an association of the extracellular environment with the impact on activation of the intracellular pathway and is in concordance with the theory of dietary factors.…”
Section: Discussionsupporting
confidence: 67%
“…Asting et al focused on defining external cell signaling and transcription factors relating to high COX-2 expression in colon cancer cells. High COX-2 expression has been connected with large differences in gene expression compared with normal colon mucosa and low COX-2 expression cells [32]. This observation indicates an association of the extracellular environment with the impact on activation of the intracellular pathway and is in concordance with the theory of dietary factors.…”
Section: Discussionsupporting
confidence: 67%
“…We did not observe promoter CpG hypermethylation in the mut p53 and COX-2 gene as it is not frequently regulated via promoter CpG methylation. Moreover, available reports suggest COX-2 promoter CpG methylation is not a frequently occurring phenomenon in cancer [28]. At the protein level, we observed over expression of COX-2 after DMBA / TPA exposure in time dependent manner.…”
Section: Original Research Article 66supporting
confidence: 52%
“…Since PGE2 is a downstream product of COX-2, it is possible to assume that the expression of COX-2 may affect the levels of PGE2. A previous study by the present authors proposed FosB as an important transcription factor in CRC patients with high COX-2 tumor tissue expression, since FosB was overexpressed in these patients, comparing with patients who exhibited low COX-2 expression (19). FosB is a member of the AP-1 complex, which has been linked to malignant transformation in several types of cancer, and its components, including FosB, have important roles on cell proliferation (among other functions), which suggests their involvement in cancer development (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by the present authors revealed that tumor tissues from CRC patients with high COX-2 expression levels displayed upregulation of several transcription factors, among which, the most overexpressed one was FBJ murine osteosarcoma viral oncogene homolog B (FosB) (19). This transcription factor is implicated in the activator protein-1 (AP-1)/COX-2/PGE2 axis, and may play a relevant role in patients with high expression levels of COX-2.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation